Perubahan Lahan Pertanian di Kelurahan Koya Barat Sebagai Pengaruh dari Peningkatan Pembangunan Infrastruktur Jalan (Jembatan Youtefa dan Jalan Ringroad) Kota Jayapura - Jibril Aqmar; Monita Yessy Beatrick Wambrauw; Tommi Tommi (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
Great infrastructure and economy development with an increasing population in the West Koya Village and the occurrence of various land changes in the West Koya Village. The purpose of this study is to identify changes in agricultural land in West Koya, to determine the effect of road infrastructure improvements on changes in agricultural land in West Koya Village and the land suitability of West Koya Village to the Jayapura City RTRW 2013-2033. This study uses a Mixed Methods approach, namely between quantitative and qualitative approaches. By using multi-year imagery from 2014-2033 to identify land changes. Using a geographic information system (GIS). The results of the research that has been carried out show that changes in agricultural land in the Koya Village occur with a reduction of 69 ha of agricultural land. Road infrastructure improvements affected changes in agricultural land in West Koya Village due to increasing land prices, locking residents to West Koya and rapid infrastructure and economy development in West Koya. The incompatibility of agricultural land in Koya Barat Village with the Jayapura City RTRW occurs with a total of 50 ha of land that is not in accordance with the 2013-2033 Jayapura City RTRW.